Nutrition Interventions for Healthy Ageing in Indonesia - Luciana Sutanto; Widjaja Lukito; Ray Wagiu Basrowi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Including Indonesia, the elderly population worldwide is on the rise. This situation is closely related to the increase in the incidence and prevalence of non-communicable diseases. Eating behavior is related to the risk of non- communicable the risk of NCDs in the elderly. Therefore, nutrition intervention should be carried out from old age.Objectives: The purpose of this study is to review potential nutritional interventions to prepare for a healthy ageing process in an Indonesian context.Discusion: This review uses social cognition theory to emphasize the importance of nutrition education, the development of nutritional products with biologically active compounds, and practical guidelines that influence individual dietary behavior. Nutritional interventions should take into account Indonesia’s existing food-based balanced nutrition diet guidelines and the dietary patterns of adults and the elderly. Indonesia has a large population, ethnic and cultural diversity, which together affect people’s daily consumption of various foods.Conclusions: Customized nutrition education programs and the development of functional foods are appropriate interventions that can be implemented in Indonesia.